ANALISIS HUKUM TENTANG PEMBATALAN HIBAH (STUDY PUTUSAN PENGADILAN AGAMA NO: 887/PDT.G/2009/PA.MDN) - PUTRI TIKA LARASARI CATURANGGA SITUMEANG (PREMISE LAW JURNAL, 2015)
Grant is to give property to another person without asking anything in return and the property is given when the owner of the property is still alive. In Indonesia, providing grant is regulated in the Article 171 (g) and Article 210 through Article 214 of the Compilation of Islamic Law. The grant that can be cancelled is the grant given by parents to their children. The data for this descriptive analytical study with normative juridical apoproach. The data obtained were analyzed through qualitative method. The factor of the cancelling a grant known at Medan Religious (Islamic) Court was that it was proven that the property did not belong to the grant provider. The decision made by the judge of Medan Religious (Islamic) Court against the case No: 887/pdt.g/2009/pa.mdn was the grant given by the wife to her husband was cancelled because of the absence of written evidence of property distribution that it was hard for the defendant to defend her resistance. Keywords: Grant, Property, Cancellation, the factor